Composite cardiovascular health indices (Life’s essential 8 and Life’s crucial 9) and female infertility: an NHANES 2013–2018 cross−sectional analysis - Duan, Yukun; Liu, Peixiu; Li, Hui; Gao, Yanping (Frontiers in Endocrinology, 2025)
BackgroundFemale infertility affects 10–15% of couples worldwide and is influenced by multiple factors, including cardiovascular and metabolic health. This study examines the association between composite cardiovascular health indices—Life’s Essential 8 (LE8) and Life’s Crucial 9(LC9)—and the risk of infertility.MethodsWe conducted a cross-sectional analysis of NHANES 2013–2018 data on 2,360 women aged 20–45 years, incorporating the NHANES complex survey design weights. We used survey−weighted multivariable logistic regression, restricted cubic splines (RCS), and subgroup/interaction analyses. For prediction, we applied LASSO with 10−fold cross−validation, followed by multivariable logistic regression to construct a nomogram. Discrimination (AUC with 95% CI), bootstrap calibration (1,000 resamples), and decision curve analysis (DCA) were reported.ResultsIn fully adjusted models, women in the highest quartile of LE8 had lower odds of infertility than those in the lowest quartile (OR 0.39, 95% CI 0.26–0.58), and similarly for LC9 (OR 0.43, 95% CI 0.29–0.65; p−trend < 0.001). The prediction nomogram showed moderate discrimination (AUC 0.691, 95% CI 0.668–0.714) with good internal calibration; no external validation was performed.ConclusionBetter composite cardiovascular health—captured by LE8 and LC9—is associated with lower prevalence of self−reported infertility. This cross-sectional design precludes causal inference. Given the nomogram’s moderate AUC and lack of external validation, the model’s clinical utility is limited. Prospective studies are warranted.